CARD 2023: expanded curation, support for machine learning, and resistome prediction at the Comprehensive Antibiotic Resistance Database. Issue Volume 51:Issue D1(2023) (20th October 2022) - Alcock, Brian P; Huynh, William; Chalil, Romeo; Smith, Keaton W; Raphenya, Amogelang R; Wlodarski, Mateusz A; Edalatmand, Arman; Petkau, Aaron; Syed, Sohaib A; Tsang, Kara K; Baker, Sheridan J C; Dave, Mugdha; et al.
Abstract: The Comprehensive Antibiotic Resistance Database (CARD; card.mcmaster.ca) combines the Antibiotic Resistance Ontology (ARO) with curated AMR gene (ARG) sequences and resistance-conferring mutations to provide an informatics framework for annotation and interpretation of resistomes. As of version 3.2.4, CARD encompasses 6627 ontology terms, 5010 reference sequences, 1933 mutations, 3004 publications, and 5057 AMR detection models that can be used by the accompanying Resistance Gene Identifier (RGI) software to annotate genomic or metagenomic sequences. Focused curation enhancements since 2020 include expanded β-lactamase curation, incorporation of likelihood-based AMR mutations for Mycobacterium tuberculosis, addition of disinfectants and antiseptics plus their associated ARGs, and systematic curation of resistance-modifying agents. This expanded curation includes 180 new AMR gene families, 15 new drug classes, 1 new resistance mechanism, and two new ontological relationships: evolutionary_variant_of and is_small_molecule_inhibitor . In silico prediction of resistomes and prevalence statistics of ARGs has been expanded to 377 pathogens, 21, 079 chromosomes, 2, 662 genomic islands, 41, 828 plasmids and 155, 606 whole-genome shotgun assemblies, resulting in collation of 322, 710 unique ARG allele sequences. New features include the CARD:Live collection of community submitted isolate resistome data and the introduction of standardized 15 character CARD Short Names for ARGs to support machine learning efforts.